MONITORIZATION TO DIABETIC CHILDREN AND DIABETIC ADOLESCENTS: ADVANTAGES AND LIMITS - Maria Helena Dantas de Menezes Guariente; Márcia Eiko Karino; Maria do Carmo Lourenço Haddad; Francismery Kasai; Carolliny Rossi de Faria; Iria Roberta Staut Freitas (Universidade Federal do Paraná, 2002)
The monitorization of the glicemic control is a fundamental part of the treatment of Diabetes Mellitus, specially in type 1 diabetics, as the metabolic control decreases or even delays chronic complications. It was elaborated a describe research with quantity approach which the purpose was appraise the practice of the glicemic monitorization between children and adolescents whose they have been assisted in a interdisciplinary program of the "Ambulatório Hospital das Clínicas da Universidade Estadual de Londrina." An instrument was used to verify the frequency of the accomplishment of the monitorization and the difficulties found for its effectivation. The sample was constituted of 63 diabetics, 47 (74,6%) adolescents and 16 (25,4%) children. It was concluded that in these population, the monitorization is very distant from the ideal. This information mobilized all persones from the team multiprofessional in the continuity of the work of pointing out the importance of the glicemic control, assisting the diabetics in the search of alternatives for the overcoming of the difficulties from emotional, economical and social order, that make difficult the accomplishment the procedure.